Differential Gene Expression in Longissimus Dorsi Muscle of Hanwoo Steers—New Insight in Genes Involved in Marbling Development at Younger Ages - de las Heras-Saldana, Sara (Genes (Basel), 2020)
The Korean Hanwoo breed possesses a high capacity to accumulate intramuscular fat, which is measured as a marbling score in the beef industry. Unfortunately, the development of marbling is not completely understood and the identification of differentially expressed genes at an early age is required to better understand this trait. In this study, we took muscle samples from 12 Hanwoo steers at the age of 18 and 30 months. From the contrast between age and marbling score, we identified in total 1883 differentially expressed genes (FDR < 0.05 and logarithm fold change ≥ 1.5) with 782 genes up-regulated and 1101 down-regulated. Differences in gene expression were higher between the ages x marbling groups rather than between high and low marbling groups. At 18 months of age, the genes SLC38A4, ABCA10, APOL6, and two novel genes (ENSBTAG00000015330 and ENSBTAG00000046041) were up-regulated in the high marbling group. From the protein–protein interaction network analysis, we identified unique networks when comparing marbling scores between different ages. Nineteen genes (AGT, SERPINE1, ADORA1, FOS, LEP, FOXO1, FOXO3, ADIPOQ, ITGA1, SDC1, SDC4, ITGB3, ITGB4, CXCL10, ACTG2, MX1, EDN1, ACTA2, and ESPL1) were identified to have an important role in marbling development. Further analyses are needed to better understand the role of these genes.